Computational simulation of cephalomedullary nailing in the osteoporotic Asian femur and clinical implications. Issue 3 (March 2022) - Chon, Chang-Soo; Kim, Joon-Woo; Sohn, Hoon-Sang; Jung, Gu-Hee
Abstract: Purpose: To assess the conformity of PFNA-II® and introduce clinical implications of new cephalomedullary nail (CMN) by analyzing three-dimensional (3D) modeling with virtual implantation at the actual size. Materials and methods: Thirty-four patients (average age; 79 years, range 68–94 years) who sustained the intertrochanteric fracture of the femur were enrolled in the present study. After importing into Mimics® software, the intact femurs on the opposite side were selected as cropping areas to reconstruct the 3D femur model with the medullary canal. PFNA-II® and new CMNs (lateral angle 0° and 2°, CCD angle 130°; CMN0° and CMN2°) were processed at the actual size and ideally placed in the proximal femur using Mimics® software. The virtual entry point (EP), nail conformity, and anatomical relationships with the adjacent structures were assessed. Results: The virtual EP of PFNA-II® was placed along the cervico-trochanteric (CT) junction in the posterior half around trochanteric fossa and always medial to the tip of greater trochanter (GT). There were six abutments in PFNA-II® models, one impingement in CMN 0°, and no impingement in CMN 2°. All the models with cortical abutment showed increased anterior and lateral bowing of the proximal shaft owing to age-dependent changes. Compared with PFNA-II®, with a decreasing tendency on the mediolateral angle of new CMNs, the virtual EP shifted to the medial and anterior side towards the CT junction. By simulating the intentional positioning in the media-to-lateral direction, the abutments in the PFNA-II® model could not be avoided. Furthermore, the lag screw of CMN 0° was placed ideally at the center or inferior side of the femoral head < 10 mm in any direction without a cortical abutment. Conclusion: To avoid cortical abutment of CMN in the Asian geriatric femur, the virtual EP would be technically placed in the medial to the GT tip, and the implant design should be changed to decrease the mediolateral angle.